2015
DOI: 10.1038/srep07726
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of elastic and inelastic energy loss on ion track formation in SrTiO3

Abstract: While the interaction of energetic ions with solids is well known to result in inelastic energy loss to electrons and elastic energy loss to atomic nuclei in the solid, the coupled effects of these energy losses on defect production, nanostructure evolution and phase transformations in ionic and covalently bonded materials are complex and not well understood due to dependencies on electron-electron scattering processes, electron-phonon coupling, localized electronic excitations, diffusivity of charged defects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 36 publications
6
75
0
Order By: Relevance
“…Also noticeable is the size difference between the first and second ion track with the second track being significantly larger. Recent results on SrTiO 3 [10] shows enhanced track formation in the presence of existing defects caused by low energy ion implantation. The authors suggest that this is due to a reduction of thermal conductivity and an increase in electron-phonon coupling due to the defects which consequently enhances the local thermal spike due to the passage of a swift heavy ion.…”
Section: Experimental and Simulationsmentioning
confidence: 98%
“…Also noticeable is the size difference between the first and second ion track with the second track being significantly larger. Recent results on SrTiO 3 [10] shows enhanced track formation in the presence of existing defects caused by low energy ion implantation. The authors suggest that this is due to a reduction of thermal conductivity and an increase in electron-phonon coupling due to the defects which consequently enhances the local thermal spike due to the passage of a swift heavy ion.…”
Section: Experimental and Simulationsmentioning
confidence: 98%
“…The importance of the coupling of electronic and atomic processes in ionic and covalent materials has been emphasized in recent studies [3][4][5][6][7][8][9][10][11][12][13][14][15]1], where it has been shown that these effects can have linearly additive [3][4][5][6][7][8] or competing [9][10][11] impacts on the defect production. A more recent study by Weber et al [16] reveals a remarkable synergy between the inelastic energy loss and pre-existing damage, showing that the presence of pre-existing disorder in the system enhances the sensitivity of the material to the electronic energy loss effects. Furthermore, we previously showed [17] that the size of nanoscale ion tracks can be controlled by the concentration of pre-existing disorder in pre-damaged SrTiO 3 systems.…”
mentioning
confidence: 97%
“…Ion tracks are of great technological interest in a wide variety of applications, such as etching and nanofabrication, sensor applications, creation of interfaces that exhibit increased conductivity, and in superconducting materials for the creation of pinning centers. [1][2][3][4] While ions of energy near or in the range of GeV are usually used for the creation of ion tracks, recent studies [4][5][6] have shown that the energy-loss threshold for ion track formation is significantly decreased in SrTiO 3 , from 20-50 keV/nm to 7-10 keV/nm, when pre-existing disorder acts synergistically with the electronic energy loss from 12 MeV Ti, 20 MeV Ti and 21 MeV Ni ions. Understanding how to control the ion track formation threshold and the ion track morphology by introducing defects in the system can allow the wider use of intermediate energy ions that are accessible in industry and research for ion beam modification of materials and creation of functionalities.…”
Section: Introductionmentioning
confidence: 99%